2008
DOI: 10.1371/journal.pone.0002073
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogenic Pseudomonads Influence Multitrophic Interactions in the Rhizosphere

Abstract: In the rhizosphere, plant roots cope with both pathogenic and beneficial bacterial interactions. The exometabolite production in certain bacterial species may regulate root growth and other root-microbe interactions in the rhizosphere. Here, we elucidated the role of cyanide production in pseudomonad virulence affecting plant root growth and other rhizospheric processes. Exposure of Arabidopsis thaliana Col-0 seedlings to both direct (with KCN) and indirect forms of cyanide from different pseudomonad strains c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 64 publications
2
38
0
1
Order By: Relevance
“…Contrary to the role of HCN as abiocontrol agent, several researchers concluded that HCN is hardly a universal biocontrol agent and even caused phytotoxic effects in most in vitro experiments (Alström and Burns, 1989;Pal et al, 2000;Kremer and Souissi, 2001;Rudrappa et al, 2008;Blom et al, 2011). In a recent study by Rijavec and Lapanje (2016) have shown that there is no correlation between the amount of HCN produced by a particular strain and its ability to inhibit the growth of phytopathogenic bacteria or fungi.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the role of HCN as abiocontrol agent, several researchers concluded that HCN is hardly a universal biocontrol agent and even caused phytotoxic effects in most in vitro experiments (Alström and Burns, 1989;Pal et al, 2000;Kremer and Souissi, 2001;Rudrappa et al, 2008;Blom et al, 2011). In a recent study by Rijavec and Lapanje (2016) have shown that there is no correlation between the amount of HCN produced by a particular strain and its ability to inhibit the growth of phytopathogenic bacteria or fungi.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
“…ACCD activity was detected according to the method of Safronova et al, (2006). The bacteria were grown in test tube containing 100 ml of liquid medium: KH 2 PO 4 (2g), K 2 HPO 4 (0.5g), MgSO 4 (0.2g), Glucose (0.2g).…”
Section: Accd Activitymentioning
confidence: 99%
“…Other physiological traits of PSM involve the release of cyanide, a secondary metabolite which is ecologically important (Wani et al 2007b) and gives a selective advantage to the producing strains (Rudrappa et al 2008;Badawi et al 2011). …”
Section: Physiological Functions Of Phosphate-solubilizing Microorganmentioning
confidence: 99%
“…However, early reports proposed that the observed phytotoxicity of P. aeruginosa strains might be due to HCN production (1,3,4,9,23,37). More recently, Rudrappa et al (35) analyzed the effect of cyanogenic pseudomonads on A. thaliana seedlings. These authors observed reduced root growth in the presence of two Pseudomonas strains (P. aeruginosa PAO1 and P. fluorescens CHA0) but normal growth in the presence of the respective HCN-defective mutants.…”
mentioning
confidence: 99%